Obsessed with the doctoral theses supervision and support during the dissertation process - Springerlink (Online service). (Rotterdam SensePublishers, 2011)
After having supervised the 30th doctoral thesis at the University of Lapland, Finland, Professor Kaarina Määttä invited the doctoral graduates and their circle of acquaintances to talk about their experiences of the process of writing a doctoral thesis and their opinions on good supervision and support. What did the dissertation process give and demand? Those who can answer this question are the ones who have defended their doctoral theses as well as the candidates? spouses and professionals in the scientific community. This book introduces explicitly all the phases of graduating as a doctor, reveals the personal matters concerning doctoral theses, and concretizes the pedagogy of supervising doctoral theses. This book is aimed at doctoral students and their professors as well as everyone who is somehow connected to the dissertation process. The aim of this anthology is to support prospective doctoral students and their supervisors in their dissertation process
Postscript Going with the research flow from master's thesis to doctoral thesis and beyond
Includes bibliographical references
Keywords: Dissertations, Academic; Graduate students -- Supervision of